2012
DOI: 10.1080/13607863.2011.651439
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of perceived lack of choice in becoming an informal caregiver

Abstract: Objectives Using data from a national sample of informal caregivers to older adults, we identify predictors of lack of choice and the consequences of lack of choice in taking on the caregiving role. Methods A national telephone survey with 1397 caregivers was carried out to assess whether respondents had a choice in taking on the caregiving role, their demographic characteristics, the nature and duration of their caregiving experience, and its impact on their physical and psychological well-being. We compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 24 publications
8
104
2
7
Order By: Relevance
“…The lack of alternative caregivers as a motive only applied to 5 % of the child caregivers (Table 1), but appeared to be a very special reason to feel more burdened. It reflects that these child caregivers may feel forced into the caregiving tasks and that lack of choice is associated with worse outcomes for care evaluation as it is for health and wellbeing (Schulz et al 2012). Helping them to mobilize other informal and formal caregivers may reduce the level of burden in this particular group of caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of alternative caregivers as a motive only applied to 5 % of the child caregivers (Table 1), but appeared to be a very special reason to feel more burdened. It reflects that these child caregivers may feel forced into the caregiving tasks and that lack of choice is associated with worse outcomes for care evaluation as it is for health and wellbeing (Schulz et al 2012). Helping them to mobilize other informal and formal caregivers may reduce the level of burden in this particular group of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the current knowledge on care evaluation is mostly focused on spouses and adult children as caregivers (Kramer 1997a;Lawton et al 1991;Marks et al 2002;Pinquart and Sörensen 2011;Raschick and Ingersoll-Dayton 2004;Savundranayagam et al 2011), we added more insight into the characteristics of the group of other caregivers, a rather unexplored type of caregiver so far (cf Schulz et al 2012). In addition, the study explored the impact of many different types of correlates, which provided more insight in differential effects on burden and positive evaluation and the degree to which the caregiver stress model is applicable to both positive and negative care evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A smaller number of studies have found beneficial effects of choice on individuals' well-being (e.g., Meng & Ma, 2015;Quine, Wells, de Vaus, & Kendig, 2007). Conversely, experiencing a lack of choice has been found to relate to maladjustment, including emotional stress, physical strain, and decreased health (Schulz et al, 2012).Having a sense of choice may be particularly important in autonomy-restrictive settings, where afforded choice can increase individuals' rather limited sense of autonomy. In a now-classic study, Langer and Rodin (1976) experimentally examined the role of afforded choice in an autonomy-restrictive context, namely among nursing home residents.…”
mentioning
confidence: 99%